2009
DOI: 10.1021/ja806869x
|View full text |Cite
|
Sign up to set email alerts
|

Structure/Function Relationships in Dyes for Solar Energy Conversion: A Two-Atom Change in Dye Structure and the Mechanism for Its Effect on Cell Voltage

Abstract: Recombination between injected electrons and iodine limits the photovoltage in dye-sensitized solar cells (DSSCs). We have recently suggested that many new dye molecules, intended to improve DSSCs, can accelerate this reaction, negating the expected improvement (J. Am. Chem. Soc. 2008, 130, 2907). Here we study two dyes with only a two-atom change in the structure, yet which give different V(oc)s. Using a range of measurements we show conclusively that the change in V(oc) is due solely to the increase in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
225
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(230 citation statements)
references
References 39 publications
4
225
0
1
Order By: Relevance
“…The DSC with TG6 exhibited 20 mV lower V OC than the DSC with K19. 26 With all the rest of the parameters identical, this result was solely related to the 2.3 times lower recombination lifetime in the case of TG6. The same effect was shown to take place for the donor (D)−π−acceptor (A) organic dyes, where additional thiophene (T3 in comparison to T1 in Figure 2) moiety in the π-bridge results in V OC reduction.…”
Section: ■ Introductionmentioning
confidence: 87%
“…The DSC with TG6 exhibited 20 mV lower V OC than the DSC with K19. 26 With all the rest of the parameters identical, this result was solely related to the 2.3 times lower recombination lifetime in the case of TG6. The same effect was shown to take place for the donor (D)−π−acceptor (A) organic dyes, where additional thiophene (T3 in comparison to T1 in Figure 2) moiety in the π-bridge results in V OC reduction.…”
Section: ■ Introductionmentioning
confidence: 87%
“…It has been observed that some otherwise efficient dyes increase the recombination rate, 25 and recombination also produces a strong limitation for solid-state 27 Although he succeeded in making the main point, the oc V of the ferrocene sample was considerable less than that of I -/ I 3 -, despite the ferrocene being 270 mV deeper (see Fig. 2).…”
Section: Nhe Vmentioning
confidence: 97%
“…They observed that the presence of an amine AR24 (Scheme 6) group in the sensitizer can significantly aggravate the charge recombination because of its strong iodide binding capability (Reynal et al 2008). In addition, they found that the charge recombination of the sensitizer with an lkoxy group (K19) was clearly more serious than for the alky sulfide substitute (TG6) (O'Regan et al 2009a). The difference was attributed to the different complexation capability with iodide of the sensitizer.…”
Section: Wwwintechopencommentioning
confidence: 99%